2021
DOI: 10.1002/acn3.51381
|View full text |Cite
|
Sign up to set email alerts
|

Loss‐of‐function variants in Kv11.1 cardiac channels as a biomarker for SUDEP

Abstract: Objective: To compare the frequency and impact on the channel function of KCNH2 variants in SUDEP patients with epilepsy controls comprising patients older than 50 years, a group with low SUDEP risk, and establish loss-offunction KCNH2 variants as predictive biomarkers of SUDEP risk. Methods: We searched for KCNH2 variants with a minor allele frequency of <5%. Functional analysis in Xenopus laevis oocytes was performed for all KCNH2 variants identified. Results: KCNH2 variants were found in 11.1% (10/90) of SU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…This is particularly relevant given the upregulation of the hERG1NP in immature myocytes and the dynamic nature of hERG1 subunit abundance in the developing myocardium (4, 47, 48) and heart failure (23). hERG1 variants are enriched in cases of sudden death in the young (6, 7) and hERG1NP dysfunction could be a contributing factor in these cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is particularly relevant given the upregulation of the hERG1NP in immature myocytes and the dynamic nature of hERG1 subunit abundance in the developing myocardium (4, 47, 48) and heart failure (23). hERG1 variants are enriched in cases of sudden death in the young (6, 7) and hERG1NP dysfunction could be a contributing factor in these cases.…”
Section: Discussionmentioning
confidence: 99%
“…KCNH2 variants that reduce IKr, or off-target hERG1 channel block cause the cardiac disorder long QT syndrome (LQTS) and increase the likelihood for cardiac arrhythmia and sudden cardiac death (2,3). KCNH2 variants have also been linked with a number of causes of death in the young that may or may not be directly linked to cardiac dysfunction, including intrauterine fetal death (4), sudden infant death syndrome (SIDS) (5,6), and sudden unexplained death in epilepsy (SUDEP) (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…KCNH2 was among the top 30 genes with the greatest number of rare variants in SUDEP vs. controls ( Bagnall et al, 2016 ). There was a higher prevalence of loss-of-function (3-fold) and rare variant (11-fold) KCNH2 variants in SUDEP cases vs. epilepsy controls ( Soh et al, 2021 ). In a separate study, 13% (6:48) of SUDEP cases had non-synonymous KCNH2 and SCN5A (Na + channel) variants linked to LQT2 and LQT3, respectively ( Tu et al, 2011 ).…”
Section: Erg1 In Neuronal Physiology and Pathophysiologymentioning
confidence: 97%
“…However, recent functional studies indicate that both rare and common SCN5A and KCNQ1 variants found in SUDEP cases display varying degrees of loss or gain of function. Furthermore, KCNH2 loss of function variants with a general population allele frequency <5% show a four‐fold enrichment in SUDEP cases when compared to an alive epilepsy population older than 50 years, who are considered at low risk of SUDEP 37,38 . It has been postulated that common variants with subclinical impact could potentially increase the risk of sudden death in people with epilepsy 39 .…”
Section: Cardiac Arrhythmia Gene Variants Found In Sudepmentioning
confidence: 99%
“…Furthermore, KCNH2 loss of function variants with a general population allele frequency <5% show a four-fold enrichment in SUDEP cases when compared to an alive epilepsy population older than 50 years, who are considered at low risk of SUDEP. 37,38 It has been postulated that common variants with subclinical impact could potentially increase the risk of sudden death in people with epilepsy. 39 The distinction between unexplained sudden cardiac death in people with epilepsy and SUDEP cannot be made by postmortem investigation alone as there are no morphological or histological markers indicative of prior cardiac arrhythmias at the postmortem examination.…”
Section: Gene Variants Found In Sudepmentioning
confidence: 99%